Strategic thinking research using grounded theory - Sharif, Mohmad Yazam; Mohmad Yazam, Siti Syamsul Nurin (2018)
The aim of the study is to explore the process of strategic thinking among top leaders in six government-linked companies (GLCs) in Malaysia. Strategic thinking is about how organizational leaders make strategic decisions. This study had focused on GLCs in Malaysia. They are owned by the federal government through some government-linked investment companies (GLICs) namely Khazanah Nasional, Permodalan Nasional Berhad (PNB), Employees Provident Fund (EPF), Retirement Fund Incorporated (KWAP), Lembaga Tabung Angkatan Tentera (LTAT) and Lembaga Tabung Haji (LTH). The methodology adopted was the Grounded Theory (GT), one of the prime qualitative methods in the literature. GT could be divided into two perspectives – the Glasserian GT and the Straussian GT. After comparing the characteristics of the two GT perspectives, the researchers found that the Straussian GT perspective was more suited to track the strategic thinking process of top leaders in the selected Malaysian GLCs. The data collection was done through telephone interviews with the relevant CEOs of the organizations concerned. The interview findings showed that all the CEOs had some kind of masters’ degrees which then shaped their perceptions of strategic thinking. The emergent theory for strategic thinking in this study was the learning theory.